Literacy and Numerical Competencies of Class IV Students on Energy Source Materials - Imaniar Afifah Nur; Ghullam Hamdu; Akhmad Nugraha (Buana Pendidikan, 2022)
Learning in Indonesia still emphasizes on the memorization aspect, which makes the high-level thinking skills of students still low. Whereas literacy and numeracy competence emphasizes high-level understanding, and does not only rely on rote literacy. Therefore, the evaluation instrument formulated based on the HOTS approach can train students' problem-solving abilities. This study is intended to describe the literacy and numeracy competencies of fourth grade students in energy sources. This study used a descriptive qualitative approach with the research subjects were students and teachers of class IV SD N 2 Tuguraja. This data collection uses interview techniques, documentation studies, and tests. This study shows that students are not used to using HOTS-oriented questions because the questions made by the teacher do not contain HOTS. In the test conducted using literacy and numeracy-oriented questions which of course require students to think at a high level, based on the analysis of test results using Rasch modeling seen from the comparison of the standard deviation value with the logit value of each student, it can be seen that the ability of students in competence literacy and numeracy is still low. Ability of students in competence literacy and numeracy is still low.